An Overview of Knowledge of Traditional Medicine for Self-medication in the Community in the Era of the COVID-19 Pandemic - Pariyana; Muhammad Aziz; Mariana; Suryadi Tjekyan; Puji Rizki Suryani; Theodora Viani; Salsa Amalia (International Journal Of Community Service, 2021)
Self-medication is usually used by the community to treat minor illnesses, especially during the COVID-19 pandemic, such as fever, dizziness, cough, flu, pain, ulcers, diarrhea, and others. Most self-medication leads to inappropriate drug use. Self-medicated knowledge is the key to prevent unwanted events, one of the example is by providing education about traditional medicine for self-medication. In addition, making a plantation pharmacy is also a solution to make it easier for people to obtain traditional medicines. The method of implementing this community service activity is to provide counseling on using traditional medicine for self-medication and planting pharmacy plantation. An overview of knowledge of traditional medicine for self-medication in the community in the era of the COVID-19 pandemic is descriptive research by looking at primary data (from questionnaires) taken in a cross-sectional manner. Based on the data obtained, it can be concluded that most people have a sufficient level of knowledge (59.09%). The community has a positive attitude towards traditional medicine self-medication as evidenced by the number of respondents who answered agree from these statements. Therefore, research can be carried out as well as counseling, education and health promotion to society with a larger sample.